Evaluating risk factors for Clostridiumdifficile infection in adult and pediatric hematopoietic cell transplant recipients. Issue 1 (December 2015) - Boyle, Nicole; Magaret, Amalia; Stednick, Zach; Morrison, Alex; Butler-Wu, Susan; Zerr, Danielle; Rogers, Karin; Podczervinski, Sara; Cheng, Anqi; Wald, Anna; Pergam, Steven
Abstract Background Although hematopoietic cell transplant (HCT) recipients are routinely exposed to classic risk factors forClostridium difficile infection (CDI), few studies have assessed CDI risk in these high-risk patients, and data are especially lacking for pediatric HCT recipients. We aimed to determine incidence and risk factors for CDI in adult and pediatric allogeneic HCT recipients. Methods CDI was defined as having diarrhea that tested positive forC. difficile via PCR, cytotoxin assay, or dual enzyme immunoassays. We included all patients who received an allogeneic HCT from 2008 to 2012 at the Fred Hutchinson Cancer Research Center; those <1 year old or with CDI within 8 weeks pre-HCT were excluded. Patients were categorized by transplanting hospital ("adult" or "pediatric") and followed for 100 days post-HCT. Results Of 1182 HCT recipients, CDI was diagnosed in 17 % (33/192) of pediatric recipients for an incidence of 20 per 10, 000 patient-days, and 11 % (107/990) of adult recipients for an incidence of 12 per 10, 000. Pediatric recipients were diagnosed a median of 51 days (interquartile range [IQR]: 5, 72) after HCT and adults at 16 days (IQR = 5, 49). Compared with calendar year 2008, pediatric recipients transplanted in 2012 were at increased risk for CDI (hazard ratio [HR] = 3.99, p =.02). Myeloablative conditioning increased CDI risk in adult recipients (HR = 1.81, p =.005). Conclusions Pediatric and adult allogeneic recipients are at high risk of CDI post-HCT, particularly adult recipients of myeloablative conditioning. Differences in CDI incidence between children and adults may have resulted from exposure differences related to age; therefore, separately evaluating these groups should be considered in future CDI studies.